Efektivitas Pemanfaatan E-Journal Mahasiswa Pascasarjana Universitas Negeri Malang - Inawati Inawati; Devinna Anugrah Dinanti; Diah Saras Wati; Enggar Rizki Pratama (Literatify: Trends in Library Developments, 2023)
This study aims to find out about the effectiveness of using E-Journal subscribed to UPT Library State University of Malang for Postgraduate Students. The focus of this research is in terms of the form of use and response of Postgraduate Students to E-Journals, as well as 5 (five) indicators of effectiveness as a theoretical basis for research. In this study, data collection was carried out through interviews with descriptive qualitative research methods. The data comes from six people who are Postgraduate Students at the State University of Malang. Interview data were analyzed by reducing data, presenting data, and drawing conclusions/verification. The results of the study show that the form of using E-Journal as the main and additional reference material in fulfilling information needs to complete graduate student coursework in the form of articles, theses, and dissertation. The effectiveness of the E-Journal subscribed to by the Library of State University of Malang has not fulfilled the five indicators of effectiveness. So that Postgraduate Students at State University of Malang have not fully experienced the effectiveness of the E-Journal subscribed to by the Library of State University of Malang